Implementasi Pembelajaran Pengembangan Kognitif AUD dengan Mengenal Angka 1-20 pada Anak Kelompok B - Handayani, Sri; Mariana, Mariana; Juita, Angelina Kurnia (Institut Agama Islam Sunan Giri Ponorogo, 2023)
This study aimed to analyze AUD cognitive development learning implementation by recognizing the numbers 1-20 in group B at RA Muslimat NU Mutiara Bangsa Dolopo. This study uses qualitative research methods by disclosing in-depth data through interviews, observation, and review of documents about what informants do and how to plan, implement and evaluate learning to develop numeracy skills 1-20. The study's results stated that at RA Muslimat NU Mutiara Bangsa Dolopo, in learning to develop the ability to count from 1-20 in group B, the teacher had carried out the learning planning stages, namely setting themes and determining methods. In learning, learning to develop counting 1-20 group B by using home visit services. The technique used is a play method that easily stimulates a child's brain simulation so that children can easily understand and have fun learning for RA Muslimat NU Mutiara Bangsa media in developing knowledge to count 1-20 using various media, namely counting with fingers, using number cards, and using seeds. In designing learning to measure 1-20 groups B RA Muslimat NU Mutiara Bangsa Dolopo, the teacher always evaluates, namely making observations without emphasizing the results of children's activities, but the teacher must first understand the child's abilities and continue to guide and always provide motivation to children so that cognitive abilities children can develop optimally according to the child's abilities, in this case, the ability to count 1-20.